The landscape of cancer-associated transcript fusions in adult brain tumors: a longitudinal assessment in 140 patients with cerebral gliomas and brain metastases - Metellus, Philippe; Camilla, Clara; Bialecki, Emilie; Beaufils, Nathalie; Vellutini, Christine; Pellegrino, Eric; Tomasini, Pascale; Ahluwalia, Manmeet S.; Mansouri, Alireza; Nanni, Isabelle; Ouafik, L’Houcine (Frontiers in Oncology, 2024)
Background Oncogenic fusions of neurotrophic receptor tyrosine kinase NTRK1, NTRK2, or NTRK3 genes have been found in different types of solid tumors. The treatment of patients with TRK fusion cancer with a first-generation TRK inhibitor (such as larotrectinib or entrectinib) is associated with high response rates (>75%), regardless of tumor histology and presence of metastases. Due to the efficacy of TRK inhibitor therapy of larotrectinib and entrectinib, it is clinically important to identify patients accurately and efficiently with TRK fusion cancer. In this retrospective study, we provide unique data on the incidence of oncogenic NTRK gene fusions in patients with brain metastases (BM) and gliomas. Methods 140 samples fixed and paraffin-embedded tissue (FFPE) of adult patients (59 of gliomas [17 of WHO grade II, 20 of WHO grade III and 22 glioblastomas] and 81 of brain metastasis (BM) of different primary tumors) are analyzed. Identification of NTRK gene fusions is performed using next-generation sequencing (NGS) technology using Focus RNA assay kit (Thermo Fisher Scientific). Results We identified an ETV6 (5)::NTRK3 (15) fusion event using targeted next-generation sequencing (NGS) in one of 59 glioma patient with oligodendroglioma–grade II, IDH-mutated and 1p19q co-deleted at incidence of 1.69%. Five additional patients harboring TMPRSS (2)::ERG (4) were identified in pancreatic carcinoma brain metastasis (BM), prostatic carcinoma BM, endometrium BM and oligodendroglioma (grade II), IDH-mutated and 1p19q co-deleted. A FGFR3 (17)::TACC3 (11) fusion was identified in one carcinoma breast BM. Aberrant splicing to produce EGFR exons 2-7 skipping mRNA, and MET exon 14 skipping mRNA were identified in glioblastoma and pancreas carcinoma BM, respectively. Conclusions This study provides data on the incidence of NTRK gene fusions in brain tumors, which could strongly support the relevance of innovative clinical trials with specific targeted therapies (larotrectinib, entrectinib) in this population of patients. FGFR3 (17)::TACC3 (11) rearrangement was detected in breast carcinoma BM with the possibility of using some specific targeted therapies and TMPRSS (2)::ERG (4) rearrangements occur in a subset of patients with, prostatic carcinoma BM, endometrium BM, and oligodendroglioma (grade II), IDH-mutated and 1p19q co-deleted, where there are yet no approved ERG-directed therapies.